Covenants with Allah - Rane, Halim, 1976- author. Link Link
1 online resource (270 pages)
Keywords: Covenants with Allh: Keystone of Islam explores the binding commitments between God and humanity that define the terms and conditions of human existence and coexistence. It presents an illuminating study of the Qurn, covenants of Prophet Muammad, and the historical record of Muslim governance. In this timely and ground-breaking work, Halim Rane and Ibrahim Zein recover the centrality of covenant (ahd and mthq) in Islam and its enduring imperative for ensuring accountability, building trust, upholding justice, and safeguarding peace and security.In an era of profound global fracture and moral uncertainty, this book demonstrates that covenants are not peripheral but foundational to Islam's theological and ethical architecture. It reveals how the Qurn's covenantal ethos shaped Muslim consciousness, diplomacy, and interreligious relations-and how the violation of modern covenants and treaties threatens the very foundations of international law, justice, and order. Bold and urgent, rigorous but accessible, this is essential reading for anyone concerned with Islam, global justice, and our shared humanity.